Histopathology of intestinal tissue of host Capra hircus caused by anoplocephalidean Cestode Stilesia - Balbhim Bhure, Sanjay Shamrao Nanware* and Dhanraj (Journal of Experimental Sciences, 2011)
The present work was conducted to study the histopathological changes in the intestine of Capra hircus, naturally infected with the Anoplocephalidean cestode, Stilesia (Railliet, 1892). It has been seen that the cestode Stilesia jadhavae. are not successful in adhering firmly to the intestinal tissue suffering that the worm is not having very close contact but they has developed very weak contact and attached loosly to crypts of Liberkhun. Not much effort is put by the parasite to survive in the intestine and the scolex is not so much helpful. It seems that the environment of the intestine is quite favourable for the worm Stilesia jadhavae which is rich in protein, glucose and fat content. So the worm finds it easy to absorb the same through tegument for grouth and nourishment.